Return of spontaneous circulation with a compression:ventilation ratio of 15:2 versus 3:1 in newborn pigs with cardiac arrest due to asphyxia. Issue 6 (10th March 2011) - Solevåg, Anne L; Dannevig, Ingrid; Wyckoff, Myra; Saugstad, Ola D; Nakstad, Britt
Abstract : Objective: International guidelines recommend a compression to ventilation (C:V) ratio of 3:1 in neonates, and 15:2 for other paediatric age groups. The authors aimed to compare these two C:V ratios in a neonatal swine model of cardiac arrest following asphyxia. Design: Experimental animal study. Setting: Facility for animal research. Subjects: 22 newborn pigs (age 12–36 h, weight 2.0–2.7 kg). Interventions: Progressive asphyxia until asystole. Animals were randomised to receive C:V 3:1 (n=11) or 15:2 (n=11). Main outcome measures: Return of spontaneous circulation (ROSC) was defined as a heart rate ≥100 bpm. Also of interest were haemodynamic parameters, cerebral and systemic oxygen saturation and the proinflammatory cytokine interleukin-1β (IL-1β). Results: Two animals in each group did not achieve ROSC. Mean (SD) increase in diastolic blood pressure (DBP; mm Hg) during compression cycles was significantly higher at a C:V ratio of 15:2 than 3:1 (7.1 (2.8) vs 4.8 (2.6)). Median time (IQR) to ROSC for the 3:1 group was 150 (140–180) s, and 195 (145–358) s for the 15:2 group. There were no significant differences in the temporal changes in haemodynamic parameters or oxygen saturation indices between the groups. IL-1β levels in cerebrospinal and bronchoalveolar lavage fluid was comparable between the groups. Conclusion: In neonatal pigs with asphyxia-induced cardiac arrest, the response to a C:V ratio of 15:2 is not better than the response to a C:V ratio of 3:1 despite better generation of DBP during resuscitation.